Avoiding stress on non-lexical material in nouns and verbs: predictable verb prosody in Serbo-Croatian stress standard varieties - Simonović Marko; Kager René (Linguistics)
We consider two asymmetries reported in the literature on word prosodic systems: the tendency to allow more prosodic contrast in nouns than in verbs and the tendency to avoid stress on functional material. We focus on the interaction between these two tendencies and propose a formal mechanism to handle this interaction couched in Optimality Theory. In a case study on a group of standard Serbo-Croatian varieties that have predictable stress in verbs but contrastive stress in nouns, we develop an analysis of predictable and morphologically conditioned stress assignment. Our analysis features a family of constraints militating against stress on non-lexical material on three different levels: stress on inflection proper (*Infl-Stress-1), stress on non-lexical material in the locality domain of inflection (*Infl-Stress-2), and stress on non-lexical material altogether (*Infl-Stress-3). Analyzing a class of prosodically exceptional denominal and borrowed verbs, we show that lexical-category effects exist between and within categories: denominal verbs allow exceptional preservation of nominal stress, which leads to additional prosodic contrast in this class of verbs. Finally, we explore the option of subsuming exceptionally contrast-preserving borrowed verbs under denominal verbs, offering arguments in favor of the hotly debated view from the literature that verbs are universally borrowed as denominal.